Sovereignty under Threat? Responsibility to Protect and the Understanding of Sovereignty - Stojkovski, Ljupcho (Journal of Law and Politics, vol.2 is.1, 2021)
The situation in Myanmar in 2019, which resulted in the mass displacement and fleeing by the Rohingya population and which, according to UN High Commissioner for Human Rights and UN Secretary General are “textbook examples of ethnic cleansing”, reignited the issue of mass atrocities and the international community’s role in dealing with these problems. The events in Myanmar are some of the latest of a series of other similar mass sufferings that have been occurring in many other places in the world, such as Burundi, South Sudan, DR Congo, Yemen, and of course Syria and Libya. It is more than obvious that this is a reoccurring problem and that is why there has to be a thorough scrutiny of the possible reasons for its persistence. This paper deals with some of these issues. It proceeds in five parts. Firstly, I give a brief introduction about the path that led to the Responsibility to Protect (R2P) and the official acceptance of R2P in 2005. Next, I underline some of the reoccurring critiques of R2P, following which, I address three of them: that R2P is a Western concept, that R2P is basically the same as humanitarian intervention and that (therefore) R2P is a threat to sovereignty. I conclude that R2P has diverse origins; that R2P is broader than humanitarian intervention; and that R2P is not a threat to sovereignty.
Keywords: Responsibility to Protect (R2P); Sovereignty